The induction and maintenance of transplant tolerance engages both regulatory and anergic CD4+ T cells. - Besançon, A; Baas, M; Goncalves, T; Valette, F; Waldmann, H; Chatenoud, L; You, S (Frontiers Media, 2017)
Therapeutic tolerance to self-antigens or foreign antigens is thought to depend on constant vigilance by Foxp3+ regulatory T cells (Tregs). Previous work using a pancreatic islet allograft model and a short pulse of CD3 antibody therapy has shown that CD8+ T cells become anergic and use TGFβ and coinhibitory signaling as their contribution to the tolerance process. Here, we examine the role of CD4+ T cells in tolerization by CD3 antibodies. We show that both Foxp3+ Tregs and CD4+ T cell anergy play a role in the induction of tolerance and its maintenance. Foxp3+ Tregs resisted CD3 antibody-mediated depletion, unlike intragraft Th1 CD4+ lymphocytes coexpressing granzyme B and Tbx21, which were selectively eliminated. Tregs were mandatory for induction of tolerance as their depletion at the time of CD3 antibody therapy or for a short time thereafter, by an antibody to CD25 (PC61), led to graft rejection. Early treatment with CTLA-4 antibody gave the same outcome. In contrast, neither PC61 nor anti-CTLA-4 given late, at day 100 posttransplant, reversed tolerance once established. Ablation of Foxp3 T cells after diphtheria toxin injection in tolerant Foxp3DTR recipient mice provided the same outcome. Alloreactive T cells had been rendered intrinsically unresponsive as total CD4+ or Treg-deprived CD4+ T cells from tolerant recipients were unable to mount donor-specific IFN-γ responses. In addition, intragraft Treg-deprived CD4+ T cells lacked proliferative capacities, expressed high levels of the inhibitory receptor PD-1, and exhibited a CD73hiFR4hi phenotype, thus reflecting a state of T cell anergy. We conclude that Tregs play a substantive and critical role in guiding the immune system toward tolerance of the allograft, when induced by CD3 antibody, but are less important for maintenance of the tolerant state, where T cell anergy appears sufficient.